2023
DOI: 10.3390/molecules28031511
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methylene Blue from Water Using Magnetic GTL-Derived Biosolids: Study of Adsorption Isotherms and Kinetic Models

Abstract: Global waste production is significantly rising with the increase in population. Efforts are being made to utilize waste in meaningful ways and increase its economic value. This research makes one such effort by utilizing gas-to-liquid (GTL)-derived biosolids, a significant waste produced from the wastewater treatment process. To understand the surface properties, the biosolid waste (BS) that is activated directly using potassium carbonate, labelled as KBS, has been characterized using scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…A similar behavior was found for the sorption of MB onto bentonite [69], peanut-shell-based activated carbon [70], and iron-oxide-modified montmorillonite [71]. In contrast, an exothermic sorption of MB was observed, for example, in the presence of bone char [72], citrate-modified pomelo peel [73], and a magnetic-gas-to-liquid-derived biosolid [74].…”
Section: Sorption Thermodynamicssupporting
confidence: 68%
“…A similar behavior was found for the sorption of MB onto bentonite [69], peanut-shell-based activated carbon [70], and iron-oxide-modified montmorillonite [71]. In contrast, an exothermic sorption of MB was observed, for example, in the presence of bone char [72], citrate-modified pomelo peel [73], and a magnetic-gas-to-liquid-derived biosolid [74].…”
Section: Sorption Thermodynamicssupporting
confidence: 68%
“…This effect indicates that the adsorption reaction is exothermic in nature, and this may be due to an increase in the kinetic energy of dye molecules with the increase in solution temperature, which ultimately reduces the strength of interaction between adsorbate dye molecules and the active sites of adsorbent magnetic "BC/Fe" nanocomposite materials with the temperature rise [8]. Similar temperature effects on MB dye adsorption by nanomagnetic adsorbents were observed by various investigators [8,44].…”
Section: Effect Of Solution Temperaturesupporting
confidence: 54%
“…Many studies have shown that bio-carbon nanocomposites are effective in removing a wide range of dyes, but methylene blue is the most commonly used model dye. [104][105][106]…”
Section: Adsorption Of Dyesmentioning
confidence: 99%